Hubungan Dukungan Sosial dengan Resiliensi Mantan Pecandu Narkoba di Surabaya - Fauziah Fitri Hernanto; Agung Putri Harsa Satya Nugraha; Roby Aji Permana (2021)
Drug abuse can interfere with a person's physical and psychological capacities. Psychological problems that can occur in a drug addict is a disturbance in the thought process. a former drug addict must have self-defense by removing a source of strength from within him which is called resilience. Social support is one of the protective factors in the process of building resilience. This study aims to analyze the relationship between social support and the resilience of former drug addicts in Surabaya. The design of this research is cross sectional with a sample size of 30 respondents. Statistical analysis used is Spearman rank correlation. Spearman rank correlation test results show the correlation coefficient value is 0.364 with a significance level of 0.048 which means that there is a relationship between social and resilience of former drug addicts in Surabaya. The correlation value of social support with the resilience of former drug addicts in this study is in the low category. Good social support is not enough to help former drug addicts to completely break away from drugs and needs to be strengthened by other external factors.